1996
DOI: 10.3109/03008209609029173
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Amelogenin Promoter: Developmentally Regulated Expression in Transgenic Animals

Abstract: We are interested in understanding hierarchical regulation pathways that control gene expression in developing teeth. In pursuit of the molecular basis for the regulated expression of amelogenin by developing ameloblasts during tooth formation, we isolated the murine amelogenin promoter. Analysis of this promoter will provide additional details towards the identification of signals generated through instructive-, dissimilar-germ layer interactions that are for responsible for temporal- and spatial-regulation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 14 publications
4
46
0
Order By: Relevance
“…3). Similar expression patterns have been seen in all transgenic animal lines that involve the amelogenin promoter, which is regulated in a tissue-specific manner (22,26,32). Using an antibody to amelogenin protein (26), no gross quantitative or qualitative changes to the expression pattern for the endogenous amelogenin gene were observed (data not shown).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…3). Similar expression patterns have been seen in all transgenic animal lines that involve the amelogenin promoter, which is regulated in a tissue-specific manner (22,26,32). Using an antibody to amelogenin protein (26), no gross quantitative or qualitative changes to the expression pattern for the endogenous amelogenin gene were observed (data not shown).…”
Section: Resultssupporting
confidence: 66%
“…Concentration and reaction conditions used for these antibodies were as recommended by the manufacturer. Essentially, identical data were obtained from animals bearing each of the transgenes, and this tissue-specific expression pattern has been reported previously for a number of transgenic animal lines (22,26,32). Tissue sections were counterstained with hematoxylin prior to photographing.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…The murine amelogenin promoter has been isolated from the mouse X-chromosome. Based upon transgenic mouse studies, our laboratory has demonstrated that the 2,263 nucleotides upstream of amelogenin start codon fully recapitulate the endogenous amelogenin gene expression profile within time and space (8). Deletion analysis of this 2,263-nucleotide stretch demonstrates that the Ϫ70/ ϩ52-bp minimal promoter is indispensable for maintaining transcriptional activity.…”
mentioning
confidence: 99%